PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH PADA MATERI SEL SISWA KELAS XI SMA - Kurniadi Hamid; Muh. Amir Masruhim; Yusak Hudiyono (EDUKASI, 2020)
This research is a development research. The aim of this research is to produce a media study base on Macromedia Flash to increase the result of study for students class XI in cell course. This development research applies 4-D model which includes define stage, design stage, develop stage, and disseminate stage. Base on the result of media test, obtained a media study base on Macromedia Flash is valid according to validators and qualified: (1) the ability of teachers to manage learning was good criteria,(2) the activity of students in learning process was active,(3) classical learning completeness is achieved,(4) the respond of students in learning component was positive. The result of research in effective class base on descriptive analysis obtained result that a media study base on Macromedia Flash has been fulfilled, among others: (1) result study in class XI reach 92, 86 % students achieved completeness, (2) the ability of teachers to manage learning was good, (3) student’s activity during the class achieved good criteria, (4) the respond of students in learning was positive. Based on the results of analysis data can be concluded that media study learning model base on Macromedia Flash on cell course in class XI senior high school was good quality.